Utilization of ELISA using thioredoxin peroxidase-1 and tandem repeat proteins for diagnosis of Schistosoma japonicum infection among water buffaloes. - Jose Ma M Angeles; Yasuyuki Goto; Masashi Kirinoki; Masahito Asada; Lydia R Leonardo; Pilarita T Rivera; Elena A Villacorte; Noboru Inoue; Yuichi Chigusa; Shin-ichiro Kawazu (PLoS Neglected Tropical Diseases)
Background The presence of animal reservoirs in Schistosoma japonicum infection has been a major obstacle in the control of schistosomiasis. Previous studies have proven that the inclusion of control measures on animal reservoir hosts for schistosomiasis contributed to the decrease of human cases. Animal surveillance should therefore be included to strengthen and improve the capabilities of current serological tests. Methodology/principal findings Thioredoxin peroxidase-1 (SjTPx-1) and four tandem repeat proteins (Sj1TR, Sj2TR, Sj4TR, Sj7TR) were initially evaluated against human sera. The previous test showed high sensitivity and specificity for antibody detection against SjTPx-1 and Sj7TR. In this study, the immunodiagnostic potential of these recombinant proteins was evaluated using enzyme-linked immunoassay on 50 water buffalo serum samples collected in Cagayan, the Philippines as compared with the soluble egg antigen (SEA). For specificity, 3 goat serum samples positive with Fasciola hepatica were used and among the antigens used, only SEA showed cross-reaction. Stool PCR targeting the S. japonicum 82 bp mitochondrial NAD 1 gene was done to confirm the true positives and served as the standard test. Twenty three samples were positive for stool PCR. SjTPx-1 and Sj1TR gave the highest sensitivity among the recombinant proteins tested for water buffalo samples with 82.61% and 78.26% respectively which were higher than that of SEA (69.57%). Conclusions/significance These results prove that SjTPx-1 works both for humans and water buffaloes making it a good candidate antigen for zoonotic diagnosis. Sj1TR showed good results for water buffaloes and therefore can also be used as a possible candidate for detecting animal schistosome infection.